Local Wisdom as an Ethnomathematics Learning Approach (A study on Regency Local Wisdom) - Dwi Erna Novianti; St. Budi Waluya; Nuriana Rachmani Dewi (Universitas Negeri Semarang, 2022)
Mathematics learning experiences a paradigm shift in its development. It is followed by various mathematics learning approaches including ethnomathematical approach. Ethnomathematical approach integrates the characters and cultural literacy in mathematics learning. Therefore, it is able to instil the mathematics concepts through the cultural practice which is implemented in the learning process. One of it is conducted through the exploration of regency local wisdom that has a role in developing ethnomathematical. This study implements the concepts of regency local wisdom which is able to be adopted in ethnomathematical learning. This study is qualitative research in which the researcher observes the local wisdom of Bojonegoro regency, East Java, Indonesia. The data obtained is related with the rational stories behind the culture. Based on observation results, Bojonegoro local wisdom such as Oklik, Tengul dance, and Khayangan Api story can be integrated in mathematics learning. Understanding the local wisdom stories can potentially bring out the values of it and connect culture with mathematics. Those stories can be implemented in mathematics learning by providing HOTS (higher order thinking skill) questions which are relevant to the learning materials.